Donepezil overdose and its atypical clinical presentations: A case report - Mohammad Delirrad; Habib Ahmadi; Nader Aghakhani (Journal of Research in Clinical Medicine)
Donepezil [Aricept®] is a centrally acting reversible acetylcholinesterase inhibitor. We are reporting an unusual case of a 49-year-old male patient with a history of gastric bypass surgery who mistakenly ingested 200 mg of donepezil. During the hospital stay, atypical presentations such as tachycardia, disorientation, mydriasis, and ophthalmic myoclonus were diagnosed. He had experienced convulsions several times and developed rhabdomyolysis. The patient gradually improved under supportive management and was discharged from the hospital after seven days. The authors hope that reporting this case will provide both context for clinicians to be aware of its overdose that may be presented by atypical manifestations or side effects, along with the main muscarinic anticholinergic presentations.